Catalytic cracking of LDPE dissolved in benzene using nickel-impregnated zeolites - Wong, S. (American Chemical Society, 2016)
Among the various processes and reactor designs in polymer cracking, catalytic cracking of polymer dissolved in solvent offers interesting features. In the present research, catalytic cracking of low-density polyethylene (LDPE) dissolved in benzene in a fixed-bed reactor was studied. The catalysts used included three zeolites in original form and nickel (Ni)-impregnated forms. The LDPE conversions achieved were high (>98%) despite the short retention times. The catalytic cracking of LDPE produced liquid in the gasoline range, gases ranged from C1 to C4, and hydrogen gas. The increase in catalyst acidity improved gas yield at the expense of the liquid yield. Although high catalyst acidity had less influence toward liquid product composition, it led to higher degree of cracking of the gaseous products. The dissolution of LDPE in benzene led to high cracking rate despite short retention time and produced liquid products that can be used as fuels.